2017
DOI: 10.1101/221218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor selection dynamics in FEF explain the reaction time variance of saccades to single targets

Abstract: In studies of voluntary movement, a most elemental quantity is the reaction time (RT) between the onset of a visual stimulus and a saccade toward it. However, this RT demonstrates extremely high variability, which in spite of extensive research remains unexplained. It is well established that, when a visual target appears, oculomotor activity gradually builds up until a critical level is reached, at which point a saccade is triggered. Here, we further characterize the dynamics of this rise-to-threshold process… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Current knowledge points to a role by the OPNs in defining the threshold and controlling saccade initiation (6,38). However, thresholds vary across behavioral paradigms (8,39), raising the question of how the threshold is set in a particular condition. Furthermore, evidence that the threshold changes during the course of a trial purely based on OPN activity is limited; OPN activity increases transiently during the visual burst but only by an additional spike or two and only in a small subset of neurons (38).…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge points to a role by the OPNs in defining the threshold and controlling saccade initiation (6,38). However, thresholds vary across behavioral paradigms (8,39), raising the question of how the threshold is set in a particular condition. Furthermore, evidence that the threshold changes during the course of a trial purely based on OPN activity is limited; OPN activity increases transiently during the visual burst but only by an additional spike or two and only in a small subset of neurons (38).…”
Section: Discussionmentioning
confidence: 99%
“…The effects are huge. For example, in our own data (Hauser et al 2018), we found that the reaction time (RT) went from about 150 ± 25 ms (mean ± standard deviation) to about 250 ± 80 ms, with the error rate changing from virtually zero (99.7% right) to about 10% of incorrect saccades. The extraordinary sensitivity of the monkeys to reward asymmetry also manifests in other, low-level behavioral metrics, such as the peak saccade velocity, as well as in the swiftness with which the animals respond to changes in the asymmetry over time.…”
Section: Introductionmentioning
confidence: 80%
“…When the rewarded location changes, which happens without warning, it takes a single trial for the spatial bias to switch accordingly (when only two locations are used). This rich phenomenology is highly consistent between animals, laboratories, and task variants, and it remains stable for months, even after many thousands of trials of practice (Hauser et al 2018;Hikosaka et al 2006;Takikawa et al 2002;Watanabe et al 2001).…”
Section: Introductionmentioning
confidence: 86%
“…The 1DR task is deceptively simple (Hauser et al 2018;Hikosaka et al 2006;Lauwereyns et al 2002). The subject (a monkey, in this case) is instructed to perform an elementary action: to look at a lone, clearly visible stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, justifying the animals' behavior on the basis of an optimality principle or ideal observer model seems rather unnecessary. Furthermore, in our own laboratory, we recently developed a mechanistic model that replicates the monkeys' RT distributions as well as single-neuron activity in the frontal eye field (FEF) during performance of the 1DR task (Hauser et al 2018). This model explains the observed behavior in great quantitative detail based on dynamical interactions found in FEF.…”
Section: Introductionmentioning
confidence: 99%